Analisis Karakteristik Karbon Aktif Hasil Pirolisis Kulitkopi Robusta sebagai Karbon Pendukung Katalis PEMFC (Proton Exchange Membrane Fuel Cell) - Muhammad Taufiqurahman; Pebi Riyanto; Rany Puspita D; Raka Mahendra S; Arif Rahman S; M. Fendy Kussuma H. S (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Proton Exchange Membrane Fuel Cells (PEMFCs) are increasingly developed due to their high efficiency, power density, durability, and environmental friendliness. However, the high cost of platinum catalysts limits their widespread application. Reducing platinum usage through the development of low-cost catalyst support materials is a promising approach. Activated carbon derived from biomass offers a sustainable and economical alternative, particularly when utilizing agricultural waste such as coffee husks, which are often discarded. This study aims to evaluate the characteristics of activated carbon produced from coffee husk waste through pyrolysis as a catalyst support for PEMFCs. Pyrolysis was conducted at 400 °C, followed by chemical activation using 1 M H₃PO₄ and 1 M KOH with a residence time of 90 minutes. The resulting activated carbon was analyzed through proximate analysis to determine moisture content, ash content, volatile matter, and fixed carbon content. The results showed that activation with 1 M H₃PO₄ produced the lowest moisture content (3.4%), the lowest ash content (3.8%), and the highest fixed carbon content (60.5%), while 1 M KOH yielded the lowest volatile matter content (27.7%). Based on these results, activated carbon produced using H₃PO₄ meets the requirements of SNI No. 01/6235/2000 and demonstrates strong potential as a catalyst support material for PEMFC applications.